Isolated, individualised, and immobilised: information behaviour in the context of academic casualisation - Willson, Rebekah; Stewart-Robertson, Owen; Julien, Heidi; Given, Lisa M. (Information Research an international electronic journal, 2024)
Introduction. Universities rely increasingly on contract academic staff for teaching and research activities; yet, working in precarious conditions, these staff face significant challenges in finding relevant workplace information, in engaging with colleagues, and in building their careers. This study examines contract academic staff perceptions of precarity and workplace marginalisation, focusing on the implications of situational and environmental influences on their information practices. Method. In-depth, semi-structured interviews with 34 contract academic staff, working in various disciplines across Canadian universities, were conducted to examine their information practices. Analysis. Interview data were analysed using reflexive thematic analysis, drawing on everyday life information seeking and information marginalisation theories. Results. Results of the study show that 1) contract academic staff conduct their work within isolated information environments; 2) this isolation leads these staff to develop highly individualised information practices; and 3) the information activities of contract academic staff are often immobilised, due to the precarious contexts that shape their work and personal lives. Conclusion. Precarious employment and information marginalisation are deeply entwined for contract academic staff. This results in frustration, disappointment, and uncertainty with their work and personal circumstances. Institutional challenges can seem intractable, particularly where task-related information provision (when available) cannot address systemic concerns.